Leadership for the CFO : influence. motivate. inspire - Bunea, Emilia (Routledge, 2026)
"Most leadership books are not written with finance in mind. This one is. Written by a seasoned CFO with deep research expertise, 'Leadership for the CFO' speaks directly to the realities of leading from the top finance seat. The CFO role is changing, requiring new levels of influence across the C-suite and in organizations. More than ever, CFOs need to raise their leadership game. What motivates finance teams? What tools can a CFO use to influence non-finance stakeholders? How can finance leaders communicate with impact? What are some blind spots CFOs have when developing talent? How can finance leaders avoid being pigeonholed in their roles? How do CFOs best prepare for a CEO role? Grounded in cutting-edge leadership research, the book answers these and many other questions. It combines clear frameworks with practical tools tailored to finance leaders. These ideas are brought to life through real-world cases of finance leaders. The book includes exclusive access to selected scenes from Crossroads Life - an award-winning film, not available outside executive education, that portrays a CFO's real-world leadership journey. Essential reading for CFOs, aspiring finance executives, and anyone aiming to lead in finance"-- Provided by publisher.
Keywords: Chief financial officers.; Leadership.; elektronické knihy; electronic books